Monitoring based nonlinear system modeling of bridge–continuous welded rail interaction. (15th January 2018) - Strauss, Alfred; Karimi, Saeed; Šomodíková, Martina; Lehký, David; Novák, Drahomír; Frangopol, Dan M.; Bergmeister, Konrad
Highlights: Longitudinal loads and their influence on stresses and internal forces in continuous welded rails (CWR) connected to bridge deck has been discussed intensively. The analyses have been carried out by means of monitoring-based nonlinear finite element modeling using advanced beam–spring interaction laws. The non-linear modeling techniques show that the proofs of the rail stress with respect to predefined code based thresholds can be considered as very conservative. Abstract: The investigation of longitudinal loads and their influence on stresses and internal forces in continuous welded rails (CWR) connected to bridge deck has been discussed intensively in the last 20 years. These discussions originated from the 1995 UIC-recommendation 774-3R, and led to the introduction of the Eurocode 1. These standards are very conservative. For instance, the code used a bi-linear stiffness–displacement law for the validation of the rail–bridge structure interaction and its effects on the rail stresses lead for short bridge spans to rail interruptions. The objective of this paper is to formulate the capacities and boundary conditions of the rail–structure interaction by means of extended numerical linear and nonlinear analyses, which are not fully comprehended in the standard specifications and therefore result in conservative interaction laws. The analyses have been carried out by means of monitoring-based nonlinear finite element modeling using advanced beam–spring interaction laws and specified thermomechanical considerations for capturing the real thermal expansion of bridge structures.